Corporate Identity Management (CIM) model in Malaysian higher education sector: literature review and hypothesis development - Mohamad, Bahtiar; Abu Bakar, Hassan; Ismail, Ahmed Rageh; Halim, Haslina (Future Academy, 2016)
Corporate Identity Management (CIM) in universities has been acknowledged in marketing literature as an important area of research. Research within the current spectrum of CIM indicates some ambiguities surrounding corporate identity in higher education. However, very few studies are available in the field of corporate identity within universities. Accordingly, the objective of this study is to examine the relationships between university’s CIM and organizational performance, and also identify the relevant underlying mechanisms in Malaysian highereducation sector. Based on a review of the existing literature in a range of areas, this study proposes a conceptual model of the positive relationships between CIM activities in universities with internal brand, transformational leadership and organisational culture. The proposed conceptual model is developed based on three main theories-- social identification theory, transformational leadership theory and social learning theory.